Aplikasi Statistika Deskriptif Pada Kajian Faktor Teknis Budidaya Ikan Lele Di Kota Palembang - Yulia Puspitaa Sari; Fitra Mulia Jaya (Universitas Sriwijaya, 2019)
Palembang is a city that has the highest consumption level of catfish in South Sumatra. Most of the supply of catfish is produced by local farmers, and imported from other cities / districts in South Sumatra. Technical factors in cultivation are very influential on the amount of production of catfish farming. The technical factors include, broodstock, spawning techniques, feed, land and technology. This paper presents the results of the analysis using descriptive statistics on technical factors in catfish farming in Palembang. By using descriptive statistics, technical factor data in catfish farming becomes easier to inform and easier to understand.